2008
DOI: 10.1152/physiolgenomics.90283.2008
|View full text |Cite
|
Sign up to set email alerts
|

Renal medullary 11β-hydroxysteroid dehydrogenase type 1 in Dahl salt-sensitive hypertension

Abstract: Liu Y, Singh RJ, Usa K, Netzel BC, Liang M. Renal medullary 11␤-hydroxysteroid dehydrogenase type 1 in Dahl salt-sensitive hypertension. Physiol Genomics 36: 52-58, 2008. First published September 30, 2008 doi:10.1152/physiolgenomics.90283.2008.-The Dahl salt-sensitive rat is a widely used model of human salt-sensitive forms of hypertension. The kidney plays an important role in the pathogenesis of Dahl salt-sensitive hypertension, but the molecular mechanisms involved remain a subject of intensive investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 52 publications
2
64
0
Order By: Relevance
“…This technique has been shown to effectively deliver DNA into the renal cells without toxicity to the kidney (26,27,41,66,71). The transfection reagent in vivo jetPEI, a polyethylenimine derivative, has been used to successfully deliver DNA into renal cells in vivo in previous studies, including ours (8,29,34,63,69,70). In addition, a combination of ultrasound and different transfection reagents (19,30,40), including polyethylenimine nanoparticles (4), has been shown to significantly enhance the DNA transfection.…”
Section: Methodsmentioning
confidence: 99%
“…This technique has been shown to effectively deliver DNA into the renal cells without toxicity to the kidney (26,27,41,66,71). The transfection reagent in vivo jetPEI, a polyethylenimine derivative, has been used to successfully deliver DNA into renal cells in vivo in previous studies, including ours (8,29,34,63,69,70). In addition, a combination of ultrasound and different transfection reagents (19,30,40), including polyethylenimine nanoparticles (4), has been shown to significantly enhance the DNA transfection.…”
Section: Methodsmentioning
confidence: 99%
“…This is illustrated by our previous work on molecular networks underlying Dahl salt-sensitive hypertension, which has led to several novel discoveries regarding the overall network (9) and specific components of the network (11,20,22,23).…”
mentioning
confidence: 93%
“…Several biological pathways have been found that may contribute to the protection from salt-induced hypertension and/or renal injury observed in the consomic BN strain compared with SS rats. Examples include attenuated oxidative stress (20), reduced local levels of glucocorticoids (11), and improved fumarate metabolism (22,23).…”
mentioning
confidence: 99%
“…Cortisol and 11 -HSDs have been implicated in hypertension (Anagnostis et al, 2009;Andrews et al, 2003;Campino et al, 2010;Cicala & Mantero, 2010;Edwards et al, 1988;Ferrari, 2010;Franks et al, 2004;Funder et al, 1988;Gathercole & Stewart, 2010;Y. Liu et al, 2008;Malavasi et al, 2010;Millis, 2011;Monder et al, 1989;Morales et al, 2008;Mune et al, 1995;Palermo et al, 2004;Paterson et al, 2004;Quinkler & Stewart, 2003;Raff & Findling, 2003;Stewart et al, 1996;Walker & Andrew, 2006;Walker et al, 1993;Wallerath et al, 1999;White et al, 1997).…”
Section: β-Hsd1 and Hypertensionmentioning
confidence: 99%
“…Liu et al showed that suppression of 11 -HSD1 expression in the renal medulla attenuates salt-induced hypertension in Dahl salt-sensitive rats (Y. Liu et al, 2008). Taking into consideration that diet is one important factor on MetSyn development, it is interesting to mention that in Dahl salt-sensitive hypertensive rats, fed a high-salt diet for 4 weeks, perirenal AT corticosterone concentration and 11 -HSD1 activity as well as GR, 11 -HSD1 and TNF-expression increase when compared with Dahl salt-resistant rats fed the same diet (Usukura et al, 2009).…”
Section: β-Hsd1 and Hypertensionmentioning
confidence: 99%